60+25x=35x+29

Simple and best practice solution for 60+25x=35x+29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 60+25x=35x+29 equation:


Simplifying
60 + 25x = 35x + 29

Reorder the terms:
60 + 25x = 29 + 35x

Solving
60 + 25x = 29 + 35x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-35x' to each side of the equation.
60 + 25x + -35x = 29 + 35x + -35x

Combine like terms: 25x + -35x = -10x
60 + -10x = 29 + 35x + -35x

Combine like terms: 35x + -35x = 0
60 + -10x = 29 + 0
60 + -10x = 29

Add '-60' to each side of the equation.
60 + -60 + -10x = 29 + -60

Combine like terms: 60 + -60 = 0
0 + -10x = 29 + -60
-10x = 29 + -60

Combine like terms: 29 + -60 = -31
-10x = -31

Divide each side by '-10'.
x = 3.1

Simplifying
x = 3.1

See similar equations:

| e^2k=3 | | 4x^4-9x^2-100=0 | | 8u-2=2u+8 | | 9-8p-8=45 | | -4y+14=-22 | | 9r+4=4+9r | | 57.95m=50.45m+60 | | W*(w+4)=60 | | 4(6x-10)=20 | | 50.45m+60=57.95 | | 2x+3(2x+11)=129 | | 4x^2+16x+32=0 | | log(x)=0.137 | | 6-n=-n+2 | | m^2+2m-36=0 | | 4x+3(x-18)=30 | | 3x^2-24x=45 | | 6t-17-4t=10 | | 4y+32=11+6y | | 6x+10=20x-8 | | 4*(n+1)=32 | | 3(8+8x)+6= | | 4k-(7+k)=-(8k+7) | | -x-14=6+3x | | 3m=3m+5 | | 6x+4(6x-12)=132 | | -21=-7/5v | | 4z+9=8 | | -3x+23=5 | | 5p+5(-5-3p)= | | 2x+2x-14=x+9+x+2+x-7 | | 9(4+v)+32v=11v |

Equations solver categories